MANIFESTATIONS OF INTERNATIONAL PECULIARITIES OF HIGHER EDUCATION DEVELOPMENT IN ARMENIA (Education in the 21st Century, 2023)
History of Tertiary Level Education spans many centuries and has its own way of development. However, its role in the lives of nations and countries has drastically increased during the last century. Taking into consideration strategic importance of education, countries have gradually paid more attention to its development.Higher education of the Republic of Armenia is in line with the manifestations of international higher education. Thus, higher education and continual growth of its quality and quantity are of great significance in Armenia.In the international arena the role of education has been more emphasized since November 1945, when UN specialized agency - UNESCO (United Nations Educational, Scientific and Cultural Organization) started its activity. The World Declaration on Higher Education for the Twenty-First Century: Vision and Action, adopted by UNESCO's World Conference on Higher Education on 9 October 1998with the aim of setting global standards on the ideals and accessibility of higher education, became the forerunner for new changes and development of higher education. A number of issues peculiar to the development of higher education are focused on in the World Declaration adopted by UNESCO and their manifestations are also existent in Armenia. One of these issues deals with strengthening of interstate cooperation in the sphere of education, and it is peculiar to the higher education of Armenia, too. After gaining independence, Armenia signed numerous interstate agreements and came closer to the international standards through reforms. Computerization of higher education is another peculiarity. Though the level of computerization of the higher education is not sufficient in Armenia yet, serious and active steps are made towards it. In the international arena the establishment of scientific and work-study institutions has become a unique form of integrity of science, education and work. In Armenia the evidence of a successful attempt to establish such institutions is cooperation of IT sphere with the leading universities of the country over the past few years.Democratization of education, i.e. existence of opportunity for every citizen of the country to receive education, is also one of peculiarities of international higher education. In Armenia higher education also tends to democratization. With this aim a number of measures have been undertaken and certain laws have been adopted. The slogan «Lifelong learning» is closely connected with democratization of education. This international slogan is also relevant to higher education of Armenia.The last significant peculiarity is humanitarization of higher education, implementation of which is evident worldwide; still, in some countries including Armenia it is expressed faintly.Thus it can be concluded that over the last three decades higher education of the Republic of Armenia has undergone drastic changes. It demonstrates peculiarities and trends of development which are in line with the international developments and they lead to integration with the international higher education.